Society and sustainability - Crowther, David; Seifi, Shahla (Developments in corporate governance and responsibility ;, 2024)
It is generally accepted that the three pillars of sustainability - economic, environmental, and social - are crucial, and must be addressed if we are to achieve sustainability in the future. Although it is generally recognised that they must be treated equally it is much less apparent that this is actualised. Most commonly concern is centred around just one pillar, presumably because most actions which benefit one pillar can have a detrimental effect on at least one of the others. Mitigating these conflicts is the most difficult aspect of sustainability, which must be addressed if we are to make satisfactory progress. In this edited collection the authors consider a number of diverse issues within the context of their implication for society and their effect on cultural issues. Given the instability of the world in the present time, both culturally and politically, all issues are explored from a variety of vital perspectives. Developments in Corporate Governance and Responsibility offers the latest research on topical issues by international experts and has practical relevance to business managers.